Examining Talent Management Practices in a Canadian Not-for-Profit Context: A Theory-Driven Template Analysis - McCaig, Melanie; Rezania, Davar; Lightheart, David (Relations industrielles / Industrial Relations, 2022)
While recognizing the importance of human capital in the success of non-profit organizations, existing research has primarily focused on talent management (TM) in large multinational organizations, mainly those in the private sectors of North America, Asia and Europe. In this article, we adopt a theory-driven approach and build on previous conceptualizations of TM to examine the perspectives of 30 Canadian nonprofit and for-profit decision-makers. Results show that Canadian decision-makers have a unique inclusive and competitive view of TM. Their view is defined predominantly by humanistic (acquired talent, inclusive, input and output) and competitive factors (reliance on recruitment and skill development). This study contributes a new perspective by providing empirical insights from managers of Canadian enterprises and pointing to implications for broader discussion, conceptualization and practice in the field.
Keywords: Canada; Développement et formation du talent; Formation inclusive; Gestion humaniste du talent; Organismes sans but lucratifs; Organismes à but non lucratif; competitive; humanistic talent management; inclusive; nonprofit; organizational nature; talent development; vision inclusive et compétitive de la formation